PENGARUH IMPLEMENTASI CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN INFORMASI PADA PERUSAHAAN YANG TERMASUK SAHAM-SAHAM LQ45 DI BEI - , Fifi Astuti Saleh ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study examined the effect of the implementation of corporate governance disclosure. Implementation of corporate governance and disclosure are two subjects that can protect investors from the asymmetry of information. In this study the sampling method used is purposive sampling is selected sample of the population with certain criteria, namely the companies included in LQ45 during 2009 and 2010. The variables tested in this study consisted of information disclosure, independent board, the structure of public ownership, audit committees and company size. The results of this study found evidence that an independent board and audit committee have a positive and significant impact on the disclosure of information while the ownership structure and firm size had no significant effect. That is, companies that provide high disclosure in annual reports.